2012
DOI: 10.1051/0004-6361/201219689
|View full text |Cite
|
Sign up to set email alerts
|

TheHerschelVirgo Cluster Survey

Abstract: Aims. We investigate the dust-to-gas mass ratio and the environmental effects on the various components of the interstellar medium for a spatially resolved sample of Virgo spirals. Methods. We have used the IRAM-30 m telescope to map over their full extent NGC 4189, NGC 4298, NGC 4388, and NGC 4299 in the 12 CO(1-0) and the 12 CO(2-1) lines. We observed the same lines in selected regions of NGC 4351, NGC 4294, and NGC 4424. The CO observations are combined with Herschel maps in 5 bands between 100-500 μm from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 79 publications
1
44
0
Order By: Relevance
“…However, environment-driven shifts in the spatial distribution of gas and dust with respect to the stellar component, as observed, e.g., in galaxies in the Virgo Cluster (Cortese et al 2012a;Pappalardo et al 2012), as well as systematic differences in the dust content of galaxies of a given mass as a function of environment, can be envisaged and represent a major source of uncertainty in the attenuation corrections applied and by extension in our analysis.…”
Section: Gas Associated With the Galaxy Upon Infallmentioning
confidence: 87%
See 2 more Smart Citations
“…However, environment-driven shifts in the spatial distribution of gas and dust with respect to the stellar component, as observed, e.g., in galaxies in the Virgo Cluster (Cortese et al 2012a;Pappalardo et al 2012), as well as systematic differences in the dust content of galaxies of a given mass as a function of environment, can be envisaged and represent a major source of uncertainty in the attenuation corrections applied and by extension in our analysis.…”
Section: Gas Associated With the Galaxy Upon Infallmentioning
confidence: 87%
“…This might account for the empirical result that the dust content of spiral galaxies in the Virgo Cluster shows a lack of strong variation as a function of cluster-centric radius Tuffs et al 2002). In addition, the observed radial gradients in the dust-to-gas ratio indicate that gas is much more efficiently removed than dust (Cortese et al 2012b;Pappalardo et al 2012), especially within the optical stellar disk. As the dust in the outer regions of the disk has a smaller effect on the observed NUV flux than that in the inner regions, this will mitigate the effect of stripping on the attenuation corrections.…”
Section: Gas Associated With the Galaxy Upon Infallmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, these observations have also revealed the spatially resolved dust properties in nearby galaxies and accordingly provided new constraints on dust evolution models in galaxies (e.g., Meixner et al 2010;Pappalardo et al 2012;P12). In spite of these significant progresses in observational studies, theoretical studies have not yet explained many of these latest new observational results.…”
Section: Introductionmentioning
confidence: 94%
“…Theoretical investigations have shown that this process can remove significant amounts of both diffuse and cold gas from within the optical radius of galaxies in rich cluster environments (Quilis et al 2000;Roediger & Brüggen 2007, 2008Tonnesen & Bryan 2009). Observational investigations have shown both dramatic stripping of the gas content of galaxies in cluster environments (Kenney & Koopmann 1999;Kenney et al 2004;Cortese et al 2011;Pappalardo et al 2012;Boselli et al 2014;Fumagalli et al 2014;Jáchym et al 2014;Jaffé et al 2015) and statistical evidence from rotation curve asymmetries in cluster galaxies with normal morphology that ram pressure stripping is likely important in those environments (Bösch et al 2013).…”
Section: Introductionmentioning
confidence: 99%